PERFORMANCE EVALUATION OF ENERGY COMPANIES WITH A NOVEL INTEGRATED MULTI-CRITERIA DECISION MAKING METHOD - MADENOĞLU, Fatma Selen; ÜNLÜSOY, Ömer Faruk; YILMAZ, Çağatay (Kafkas Universitesi Iktisadi ve Idari Bilimler Fakultesi Dergisi, 2022)
Financial statements are an important tool for assessing and analyzing an organization's financial performance. Financial performance analysis allows for an accurate and appropriate appraisal of an organization's performance. The evaluation procedure must be thoroughly stated because financial performance indicators represent a company's competitiveness. This study provides a novel integrated multi-criteria decision-making method for analyzing an organization's financial performance. The applicability of the proposed method is assessed employing financial ratios that are integrated to generate a financial performance score for eight well-known Turkish energy companies. The criteria are weighted using the entropy method in the proposed method. The multi-attributive border approximation area comparison (MABAC) method is used to rank the companies. As the weights of the criteria have an impact on the ranking outcomes, a sensitivity analysis of the weights is performed. We also exhibit a comparison analysis of energy company rankings to validate the proposed approach's results using four MCDM methods: ELECTRE, MAUT, TOPSIS, and WASPAS. In addition, an alternative weighting method is also used to evaluate the results. The results show that the proposed method is an effective MCDM for coping with evaluation problems.
Keywords: finansal oranlar; Performans Değerlendirme; Finansal Oranlar; ÇKKV; MABAC; MABAC; JEL Codes: M1; Performans değerlendirme; Performance Evaluation; Financial Ratios; MCDM; MABAC; ÇKKV; Performance evaluation; C02; financial ratios; MCDM; C44; 9. Industry and infrastructure; 7. Clean energy; 8. Economic growth